Inhibition of salty taste and sodium appetite by estrogens in spontaneously hypertensive rats - Emilson Donizete Pereira; Aline Aparecida Zenatti; José Vanderlei Menani; Laurival Antonio De Luca; Carina A. F. Andrade (Frontiers in Physiology, 2023)
Estrogen has a well-known effect of reducing salt intake in rats. This mini review focuses on recent findings regarding the interaction of estradiol with brain angiotensin II to control increased sodium palatability that occurs as a result of sodium appetite in spontaneously hypertensive rats.